The influence of automatic submerged arc welding regime parameters on the weld penetrations - Palić, Vlastimir; Bela, Sabo; Alanović, Jadranko (Journal of Production Engineering, 1991)
This paper presents the results of an investigation into the influence of the key automatic submerged arc welding parameters on weld penetration. Through experimentation, regression relationships were determined for penetration as a function of various parameters, including welding current (I), welding speed (v), and arc voltage (voltage). A statistical method for establishing regression equations classes is introduced, involving testing for linear, square, cubic, and fourth power effects of these welding parameters on weld penetration. The suitability of these regression equations was verified through statistical methods. Through dispersion, regression, and graphic analyses, it was established that welding current and welding speed have a significant impact on weld penetration, whereas arc voltage is not as influential. Both measured and calculated values are presented in tables and graphs. It’s important to note that all weldings were performed using domestic welding materials.